Stability of antimicrobial agents in an elastomeric infusion pump used for outpatient parenteral antimicrobial therapy. (February 2021) - Akahane, Mutsumi; Enoki, Yuki; Saiki, Reika; Hayashi, Yukitaka; Hiraoka, Kana; Honma, Kyoka; Itagaki, Marina; Gotoda, Mai; Shinoda, Kozue; Hanyu, Satomi; Hamamura, Yuna; Miyajima, Taichi; et al.
Highlights: CEZ, CMZ, PIPC, and TAZ were stable at 31.1 °C for 24 h when dissolved in saline and 5% dextrose solution. CEZ, CMZ, PIPC, and TAZ were also stable at 4 °C storage condition for 10 days. These antimicrobial agents did not adsorb onto the elastomeric infusion pump. DRPM and MEPM were not stable in any other infusion solution at 31.1 °C. Abstract: Objectives: The long-term stability of antimicrobials dissolved in infusion solution is necessary to establish and spread the outpatient parenteral antimicrobial therapy (OPAT). In this study, we evaluated the stability of antimicrobial agents dissolved in infusion solutions. Methods: The antimicrobial agents were dissolved in infusion solutions and kept at 25 °C and 31.1 °C for 24 h or 4 °C for 10 days in a polypropylene tube or an elastomeric infusion pump. The stability was measured by high-performance liquid chromatography. Results and conclusion: The residual ratio of cefazolin (CEZ), cefmetazole (CMZ), piperacillin (PIPC), and tazobactam (TAZ) at 31.1 °C for 24 h was as follows: 95.7 ± 3.0%, 94.8 ± 0.9%, 102.6 ± 1.8%, and 103.9 ± 3.6% in saline, respectively; 94.7 ± 3.0%, 94.3 ± 1.5%, 106.1 ± 3.0%, and 107.3 ± 2.4% in 5% dextrose solution, respectively. The residual ratio of these antimicrobials at 4 °C for 10 days was maintained above 90% in both saline and 5% dextrose solution. The residual ratio of all the above antimicrobials in an elastomeric infusion pump at 31.1 °C for 24 h was equivalent to that in the polypropylene tube. On the other hand, doripenem and meropenem were not stable in any infusion solution at 31.1 °C. CEZ, CMZ, and PIPC/TAZ dissolved in saline or 5% dextrose solution can be used in OPAT with continuous infusion pumps.